Towards global consensus in the treatment of gastrointestinal stromal tumor - Reichardt, Peter (Expert Rev Anticancer Ther, 2010)
The contemporary clinical landscape of gastrointestinal stromal tumor (GIST) has evolved rapidly over the past several years. Widely used treatment guidelines – from the European Society of Medical Oncology (ESMO) and the National Comprehensive Cancer Network – have recently been updated and represent the most up-to-date, comprehensive tools guiding the optimal management of GIST. In these, and in other published guidelines, close alignment among recommendations now exists for many of the clinical issues relevant to GIST management – surgery, use of the tyrosine kinase inhibitors imatinib and sunitinib and the role of pre- and post-operative imatinib, among others. This trend towards a global consensus in the treatment of GIST is the result of a relatively large amount of new data across the spectrum of its management. However, for some clinical considerations, recommendations still partially deviate. This review examines clinical recommendations and opinions on the management of GIST in the context of the latest data in the field and with an eye towards a multidisciplinary approach including surgical oncology, medical oncology, pathology and diagnostic radiology. Points of consensus are highlighted. Expert opinion is presented on management areas where no scientific evidence or firm recommendations currently exist; lingering and unresolved questions or issues are included. Within this framework, we present an evaluation of current global guidelines on the following areas in GIST management: surgery in the metastatic setting; neoadjuvant therapy; adjuvant therapy; mutational analysis; maintenance tyrosine kinase inhibitor therapy; and radiological imaging in GIST. A summary of consensus across these guidelines based on clinical trial data is juxtaposed with expert opinion where gaps in data still remain.